The Influence of MICE Activities on Room Occupancy Rates at Hotel Xyz - Sabina, Elvira; Widaharthana, I Putu Esa; Sumadi, I Gede (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
Hotel Xyz Bali is one of the hotels that facilitates MICE activities. Hotel Xyz in 2017 – 2024 is in fluctuating conditions every year. An increase in the number of MICE events does not necessarily increase the room occupancy rate and vice versa. This research aims to analyze the influence of MICE activities on room occupancy rates at Hotel Xyz. This research was divided into 2 periods, namely before and after the pandemic and did not use data during the pandemic because it could affect the data results. Data collection methods include documentation studies and interviews, using simple linear regression analysis, multiple regression analysis, coefficient of determination test, t test and f test. Based on the analysis results, it can be identified that MICE activities do not have a positive effect on room occupancy rates with a contribution of 1.4% before the pandemic. This result is inversely proportional to after the pandemic where it was discovered that MICE activities had a positive influence on room occupancy rates and had a contribution of 23.1%.